Neurology faculty comfort and experience with communication skills. (March 2023) - Zhang, Cen; Kurzweil, Arielle; Pleninger, Perrin; Nelson, Aaron; Gurin, Lindsey; Zabar, Sondra; Galetta, Steven L.; Balcer, Laura J.; Lewis, Ariane
Highlights: Strong communication skills are important for neurology teaching faculty. Faculty comfort with communication skills may vary with sex and tenure. Faculty development may improve familiarity with communication-based scenarios. Abstract: Background: Neurology faculty care for complex patients, teach, and work within multidisciplinary teams. It is imperative for faculty to have strong communication skills. Methods: We surveyed NYU neurology teaching faculty to determine levels of comfort and experience over the past year with providing negative feedback to a trainee; debriefing after an adverse clinical outcome; and assisting a struggling colleague. We examined the relationship between levels of comfort and experience with 1) faculty self-identified sex and 2) number of years since completion of medical training. Results: The survey was completed by 36/83 teaching neurology faculty (43 %); 17 (47 %) respondents were female and 21 (58 %) were ≤10 years post-training. The proportions of faculty who reported feeling uncomfortable were 44 % (16/36) for assisting a struggling colleague, 28 % (10/36) for providing negative feedback, and 19 % (7/36) for debriefing an adverse outcome. Proportions of faculty who reported they had no experience were 75 % (27/36) for assisting a struggling colleague, 39 % (14/36) for debriefing an adverse clinical event, and 17 % (6/36) for providing negative feedback. Female respondents and faculty who were ≤10 years post-training were more likely to report feeling uncomfortable with assisting a struggling colleague and to have had no experience doing so in the past year. On multivariate analyses accounting for sex and experience, sex remained independently associated with feeling uncomfortable with assisting a struggling colleague (OR = 12.2, 95 % CI: 2.1–69.6, p = 0.005). Conclusion: Faculty development may be needed to improve comfort and experience with challenging communication-based interactions. Female faculty and faculty early in their careers may benefit most.